Improving English Speaking Skills in Learning Descriptive Text Using Series of Pictures (psnppg, 2023)
One kind of verbal communication is speaking. By speaking, students can convey messages directly to listeners. However, there are still many students who have difficulty speaking English. One of them was experienced by class X-4 students at SMA Negeri 2 Semarang in the 2023/2024 academic year. Many of them have difficulty speaking English due to weak mastery of vocabulary, pronunciation, grammar and organization of ideas, which has an impact on their fluency when speaking. This research aims to improve students' English speaking skills using a series of pictures in learning descriptive text. This research is Classroom Action Research (CAR) which uses the model from Kemmis and McTaggart. The media used by the researcher as an example and created by students is a series of pictures which provides detailed, sequential, and structured descriptions of their friends. This research was carried out in 2 cycles. It was found that students experienced an increase in learning outcomes in cycle II with the average score in cycle I was 76.39 and cycle II was 82.08. This happened because The researcher added actions in cycle II by asking students to add detailed images or symbols that helped them remember difficult vocabulary, thus making them speak more fluently when presenting their descriptive text.
Keywords: Series of pictures; speaking skill; descriptive text